Importance and Elements of Sanghahawatthu 4 - (Samrej)*, Phrakhrudhammathon Decho Ṭhitatejo (Journal of Dhamma for Life, 2021)
This academic article aims to study the elements and importance of the Four Sangahawatthu in Buddhism. That is a principle that has always been applied to life and work in Thai society. Therefore, its importance appears in many dimensions such as living a household, making friends, helping in public affairs, working, and Social coexistence, etc. The elements of Sangahavathu are the four principles that serve as a means of conduct for unity and upkeep. Which is Dana, Piyavācā, Atthacariya, and Samanattata.